Psychosocial determinants associated with healthcare workers' self-reported compliance with infection prevention and control during the COVID-19 pandemic: a cross-sectional study in Dutch residential care facilities for people with intellectual and developmental disabilities - Famke Houben; Casper DJ den Heijer; Nicole HTM Dukers-Muijrers; Claudia Smeets-Peels; Christian JPA Hoebe (BMC, 2023)
Abstract Background Healthcare workers' (HCWs) compliance with infection prevention and control (IPC) is crucial to reduce the infection transmission risk. However, HCWs' compliance with IPC in residential care facilities (RCFs) for people with intellectual and developmental disabilities (IDDs) is known to be suboptimal. Therefore, this study examined sociodemographic and psychosocial determinants associated with IPC non-compliance in this setting, to inform IPC policy and promotion programmes for adequate IPC behaviour. Methods An online questionnaire was administered to 285 HCWs from 16 RCFs between March 2021 and March 2022. Determinants associated with IPC non-compliance were assessed using logistic regression analyses. Results Being a woman (OR: 3.57; 1.73-7.37), and being a non-medical professional were associated with increased odds of non-compliance (social workers, OR: 2.83; 1.65-4.85; behavioural specialists, OR: 6.09; 1.98-18.72). Perceived inadequate education/training (aOR: 1.62; 1.15-2.27) and perceived time constraints/competing priorities (aOR: 1.43; 1.03-1.98) were also associated with increased odds of non-compliance, independent of sociodemographic variables. In contrast, the belief that the supervisor complies with IPC (descriptive norm supervisor) was associated with decreased odds of non-compliance (aOR: 0.60; 0.41-0.88). Conclusions To improve IPC in disability care settings, the implementation of tailored and structural IPC education and training programmes (e.g., on-the-job training) is recommended to increase HCWs' capabilities and bridge the IPC compliance gap between medical and non-medical professionals. In addition, role models, particularly supervisors, are crucial for promoting IPC behaviour. Facilities should create a culture of IPC compliance by norm setting, acting on, and modelling IPC behaviours at all levels of the organisation (management, medical, and non-medical staff).